Piecrusting to Facilitate Skin Closure. Issue 4 (August 2016) - Singh, Dishan; Lomax, Adam
Wound dehiscence and infection may arise when the skin around the foot or ankle is closed under tension after a surgical incision or trauma. Two cases where a piecrusting technique, using small transdermal incisions made in the surrounding skin similar to the holes in a pie crust, are presented and a literature review of the technique has been performed. The multiple small stab incisions perpendicular to the line of tension have enabled skin closure without tension and have healed with minimal scarring. Levels of Evidence : Level V: Expert opinion